(untitled) (CAHIERS MAGELLANES-NS, 2024)
Badminton is a sport that requires a combination of physical and psychological skills, including endurance, agility, speed, strength, focus, and concentration. Playing badminton with rapid motions might lead to injuries to the muscles. For athletes, integrating yoga into their training regimens can significantly lower their risk of injury. This research aims to create, verify, and assess the feasibility of a personalized yoga program for badminton players. Objective(s): This study intended to develop a yoga module for badminton players and investigated its feasibility of the module. Materials and methods: The study was completed in four stages. This study was planned in four phases: (a) Designing of YM for badminton players (b) Validation of YM for badminton players by fifteen Subject matter (yoga) experts (SMEs) from various yoga institutes who fulfilled the study criteria, were involved in the validation process (c) Content validation ratio for validated yogic practices (d) Feasibility for Validated Yoga Module. A Structured Integrated Yoga Module for the badminton game containing 29 yoga practices was validated by 15 SMEs. As per Lawshe's CVR critical value, the minimum value for 15 experts is 0.60, this means that the CVR ratio obtained is found to be important for evaluating the content validity of the module and the module is valid for use as an intervention for badminton players, which is approved by yoga experts. Feasibility was assessed on the basis of the Unipedal Stance Test, Badminton Agility Test (BAT), and Shuttle Run Test means. Results: A paired sample t-test was conducted to test the hypothesis that yoga intervention with the validated yogic module would result in statistically significant differences in post-intervention means compared to pre-intervention means for the Unipedal Stance Test, Badminton Agility Test (BAT), and Shuttle Run Test variables. The intervention period was 1 month, with 5 days a week of practice. Conclusion: The present study offers a validated yoga module consisting of 18 practices for badminton players. The results of the pilot study suggested that the module is feasible, acceptable, and easy to practice for badminton players. We recommend that badminton players should practice this yoga module for a minimum of 40 min every day under the supervision of a yoga expert.